Polarizabilities as a test of localized approximations to the self-interaction correction - Messud, J.; Wang, Z.; Dinh, P. M.; Reinhard, Paul-Gerhard; Suraud, E. (Chemical Physics Letters, 2009)
We present applications of the recently introduced 'Generalized SIC-Slater' scheme which provides a simple self-interaction correction approximation in the framework of the optimized effective potential. We focus on the computation of static polarizabilities which are known to constitute stringent tests for density-functional theory. We apply the new method to model H chains, but also to more realistic systems such as C4 (organic) chains, and less symmetrical systems such as a Na5 (metallic) cluster. Comparison is made with other SIC schemes, especially with the standard SIC-Slater one. © 2009 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-07-24